Subsurface Structure Analysis Using HVSR Inversion in the Musi Ujan Mas Kepahiang Hydroelectric Area - Shalzabilla Umini Annaqsyabandi; Refrizon Refrizon; Arif Ismul Hadi; Muhammad Najib Syami Muqtadir; Hilmi Zakariya (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2026)
Bengkulu Province is characterized by high seismic activity due to the convergence of the Indo-Australian and Eurasian plates and the presence of the active Musi Segment of the Sumatra Fault. These tectonic conditions make Kepahiang Regency particularly susceptible to shallow earthquakes, highlighting the importance of subsurface characterization for critical infrastructure such as the Musi Ujan Mas Hydroelectric Power Plant. This study aims to investigate subsurface characteristics around the hydropower plant area using microtremor measurements analyzed through the Horizontal to Vertical Spectral Ratio (HVSR) method and HVSR inversion. A total of 40 measurement points were acquired using a PASI Gemini 2 portable seismograph with a sampling frequency of 200 Hz. HVSR analysis was conducted to determine the dominant frequency (f₀), amplification factor (A₀), and seismic vulnerability index (Kg), while inversion of HVSR curves using Dinver software was applied to estimate shear-wave velocity (Vs) profiles and   values. The results show that f₀ ranges from 1,21 to 5,77 Hz, with dominant low-frequency values indicating thick and soft sediment layers. Amplification factors vary between 1,46 and 15,01, while Kg values suggest that a large portion of the area is highly vulnerable to seismic effects.   values range from 213,26 to 508,88 m/s, corresponding to soil classes C and B based on UBC and EC8 classifications. These findings indicate significant subsurface heterogeneity and identify areas prone to seismic amplification, providing important information for seismic hazard assessment and infrastructure planning.